Bi‐Allelic COQ4 Variants Cause Adult‐Onset Ataxia‐Spasticity Spectrum Disease. Issue 10 (1st September 2022) - Cordts, Isabell; Semmler, Luisa; Prasuhn, Jannik; Seibt, Annette; Herebian, Diran; Navaratnarajah, Tharsini; Park, Joohyun; Deininger, Natalie; Laugwitz, Lucia; Göricke, Sophia L.; Lingor, Paul; Brüggemann, Norbert; et al.
Abstract: Background: COQ4 codes for a mitochondrial protein required for coenzyme Q10 (CoQ10 ) biosynthesis. Autosomal recessive COQ4 ‐associated CoQ10 deficiency leads to an early‐onset mitochondrial multi‐organ disorder. Methods: In‐house exome and genome datasets (n = 14, 303) were screened for patients with bi‐allelic variants in COQ4. Work‐up included clinical characterization and functional studies in patient‐derived cell lines. Results: Six different COQ4 variants, three of them novel, were identified in six adult patients from four different families. Three patients had a phenotype of hereditary spastic paraparesis, two sisters showed a predominant cerebellar ataxia, and one patient had mild signs of both. Studies in patient‐derived fibroblast lines revealed significantly reduced amounts of COQ4 protein, decreased CoQ10 concentrations, and elevated levels of the metabolic intermediate 6‐demethoxyubiquinone. Conclusion: We report bi‐allelic variants in COQ4 causing an adult‐onset ataxia‐spasticity spectrum phenotype and a disease course much milder than previously reported. © 2022 The Authors. Movement Disorders published by Wiley Periodicals LLC on behalf of International Parkinson and Movement Disorder Society